A constitucionalidade da norma antielisiva no direito tributário brasileiro - OLIVEIRA, Fernando Augusto Braga (Universidade Federal do Pará, 2015)
This study aims to demonstrate the constitutionally of the general rule "antielisiva" inserted in the Brazilian Law with the alteration of the article 116, already existing and the interpretation that should be accomplished in a context that needs to observe the Federal Constitution of 1988, with the several prevision of social rights. The rule brings about the matter of the individual front to social, freedom front to equality, the search of the material truth, without rights violation. lt is made an approach on the interpreter and the interpretation of the rules and pricipies, the need of application of the proportionality principles with the search of the material truth and the Fiscal Justice without violation of the fundamental warranties of the individual in special of the taxpayer. The necessary presentation to disclose positivist arguments that intentionally forget the constitutional fundamentais foressen in the 1st. and 3rd. Articles of the Federal Constitution of 1988. Paradigms and prejudices were set aside to acknowledge the sense of the "antielisiva" rule in the Brazilian Law. The demonstratiofi of the difference between the "elision" and fiscal evasion became indispensable for removing afterwards the difficulties that were the inconstitutionality allegations of the "antielisão" rule in Brazil, for possible affront to the legality and the freedom. It was used arguments on the ground of the Federal Constitution and based on the foreseen provision of the New Brazilian Civil Code After the disclosure of the respective constitutionally, based on the context, pursuant article 116, only paragraph of CTN, presenting at the end some guidelines as suggention for the application of the "antielisão" rule in the Brazilian Law. It was accomplished a doctrinary research with incursion in laws and respective jurisprudency. Intentionally to conclude, it was not made comparison with any foreign legislation, as the main purpose of this study is exclusively, the application of the rule in Brazil.